Macroeconomic Determinants of House Prices in Malaysia - Saizal Pinjaman; Mori Kogid (2020)
House prices in Malaysia are considered to be seriously unaffordable as the median all-house price is relatively higher than the annual median income. Although the issue of house prices is prevalent in the country, few studies have been done to determine factors that influence its movement. The current paper, therefore, attempts to investigate the causal relationship between macroeconomic variables and house prices in Malaysia by accounting for the existence of a structural break for the variables. It is identified that in the long run, macroeconomic variables are collectively significant in influencing house price movement while the individual impact of macroeconomic variables is varied. The rise in the level of interest rates, housing supply, and inflation will result in the decline in house prices while gross domestic product and local currency appreciation cause the price to increase. It was found that stock prices do not significantly influence house prices. Of all the macroeconomic factors analyzed, exchange rate fluctuations appear to be most significant in explaining the movement of house prices. In the short-run, all macroeconomic factors are individually significant in influencing house prices and it is also identified that house prices tend to move back into their long-run state after temporary macroeconomic shocks with the speed of adjustment around 5.2 percent quarterly. It is advised for the policymakers to constantly monitor the movement of macroeconomic factors and take necessary actions to cushion the adverse impact of the movement of house prices in the country.